PENGARUH IMPLEMENTASI TOTAL PERFORMACE SCORECARD TERHADAP KUALITAS DAN IMPILKASINYA DALAM MENINGKATKAN KINERJA PERGURUAN TINGGI - Siti Maghfiroh; Intan Imam Sutanto; Permata Ulfah (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2022)
Improvement of service quality for education institutions is one of the key factors in the competition international in this globalization era. Total Performance Scorecard (TPS) is an approach to improvement the quality continually from every business aspect and organization totality to effectively implementation of total performance scorecard to increase service quality and implication to performance. The purpose of this research are analyze and verified the effect total performance scorecard to increase service quality at higher education in central of Java and implications to performance of higher education.. The method of this research is survey method with random sampling. The data will be analyzed by using descriptive analysis and simple regression and interaction regression. The results indicate that:1) implementation of total performance scorecard have effect toward service quality, 2) the service quality have not effect toward higher education performance.